PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, REPUTASI KAP DAN OPINI AUDITOR TERHADAP TIMELINESS PELAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi yang Terdaftar di Bursa Efek Indonesia 2011-2013) - Henisa -; Yusralaini -; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of Profitability, Liquidity, Firm Size, Public Accountant Office’s Reputation and Auditor’s Opinions to timeliness of financial statement (Empirical Study On The company Infrastructure Sector, Utilities and Transport Listed in Indonesia Stock Exchange 2011-2013). The population in this study are all Companies Sector Infrastructure, Utilities and Transportation listed on the Stock Exchange. The number of sample firms 33 firms by the number of observations were 99 (33x3) observations that selected by using purposive sampling method. Data analysis using logistic regression at levels significance 5%. The results of the study concluded, liquidity and Firm Size significantly affect to timeliness of financial reporting, while variable the Profitability, Public Accountant Office’s Reputation and Auditor’s Opinions not have an affect to timeliness of financial reporting of company Infrastructure Sector, Utilities and Transport Listed in Indonesia Stock Exchange 2011-2013.Keywords: Timeliness, profitability, Liquidity, and firm size.